Analysis of the Influence of Company Size, Audit Quality, and Financial Distress on Auditor Switching (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2016-2019) - Rusgowanto, Fransisca (Tinta Emas Institute, 2023)
The purpose of this study was to obtain empirical evidence that company size, audit quality, and financial distress can affect auditor switching. The population of this study was 74 manufacturing companies listed on the Indonesia Stock Exchange for the period 2016– 2019. The sampling method used was the purposive sampling method. The number of samples that matched the research criteria were 43 manufacturing companies with a total of 172 observations. However, the analytical method used in this study is logistic regression analysis. The results of this study indicate that company size and financial distress have an effect on auditor switching. However, audit quality has no effect on auditor switching.